Effects of micronutrients (Boron, Copper, Manganese) on Ganoderma boninense suppression on oil palm seedlings measured by using proximal sensors - Mohd Zahir, Mohammad Hilmi (2015)
Ganoderma disease is known as biggest threat in the Southeast Asia country, mainly Malaysia and Indonesia. The disease is hard to control because of its characteristics that are soil borne and cannot be detected for early infection. This study was done to investigated the manipulation of micronutrients (Boron, Copper, Manganese) on Ganoderma boninense suppression, and to measure the effectiveness of proximal sensors; spectroradiometer GER 1500 and SPAD 502 Minolta on heatlh condition of Ganoderma boninense’s infected oil palm seedlings treated with Boron (B), Copper (Cu), and Manganese (Mn). The experiment was done for eight months. Tenera’s variety of oil palm seedlings was used for five treatments that are T1 (control 1, non inoculated + Basic fertilizer), T2 (control 2, inoculated + Basic fertilizer), T3 (Basic fertilizer + 3 mg B/kg of soil), T4 (Basic fertilizer + 2 mg Cu/kg of soil), and T5 (Basic fertilizer + 2 mg Mn/kg of soil). Correlation coefficient between spectral reflectance of different wavelengths and SPAD with bulb severity shows averagely high value of Pearson correlation coefficient. However, only correlation of SPAD and bulb severity shows significant difference at 0.05 significant level. The regression between SPAD and bulb severity shows the highest result of regression. This could be related to suppressed chlorophyll production and damaged cell structure with different treatment of micronutrients. T3 treatment was successful to lower the disease severity levels. Proximal sensors used in this experiment were worth to indicate early infection of Ganoderma boninense.